2021
DOI: 10.1186/s40657-021-00308-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and regional differences in migration patterns and conservation status of Swan Geese (Anser cygnoides) in the East Asian Flyway

Abstract: Background The Swan Goose (Anser cygnoides) breeds across Mongolia and adjacent China and Russia and winters exclusively in China. It is globally threatened, showing long-term major range contractions and declining abundance, linked to habitat loss and degradation. We remain ignorant about the biogeographical subpopulation structure of the species and potential differences in their migration timing, stopovers and schedules, information that could be vital to effective conservation of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Swan geese specialize on submerged tubers, which are only available when lakes have melted, although both field observations and our tracking data suggest swan geese can graze on sedges and grass (41,42). A former study observed that swan geese breeding in Eastern Mongolia (i.e., the same population as our study species) take significantly longer periods to arrive at their breeding grounds than those breeding in Central or Western Mongolian, due to a prolonged staging at the core stopover sites in the Northeast China Plain (43). Their arrival on the breeding grounds coincides with the date that minimum temperatures are above the freezing point of water (43).…”
Section: Maymentioning
confidence: 59%
“…Swan geese specialize on submerged tubers, which are only available when lakes have melted, although both field observations and our tracking data suggest swan geese can graze on sedges and grass (41,42). A former study observed that swan geese breeding in Eastern Mongolia (i.e., the same population as our study species) take significantly longer periods to arrive at their breeding grounds than those breeding in Central or Western Mongolian, due to a prolonged staging at the core stopover sites in the Northeast China Plain (43). Their arrival on the breeding grounds coincides with the date that minimum temperatures are above the freezing point of water (43).…”
Section: Maymentioning
confidence: 59%
“…Moreover, our study emphasises that food shortage may not only influence fitness of consumers through diet and foraging habitat shifts, but may also affect fitness of other animals through modification of interspecific interactions. Given the increasing important role of Poyang Lake in waterbird protection in the Yangtze River floodplain (Wang et al, 2017; Zhang et al, 2011) and the East Asian–Australasian Flyway (Damba et al, 2020; Deng et al, 2020; Li, Zhao, et al, 2020), it is urgent to reverse the broad decline of submerged macrophytes to protect waterbirds. Our study also emphasises the importance of behavioural plasticity for animals to cope with interspecific competition to respond rapidly to environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…It harbours about 420,000 waterbirds belonging to 111 species in winter (Li et al, 2019). Poyang Lake is one of the most important wintering grounds for geese, supporting about 90% of the inland population of the swan goose (Damba et al, 2020), about 50% of the East Asian population of the bean goose (Li, Zhao, et al, 2020), and 70% of the East Asian continental population of the greater white-fronted goose (Deng et al, 2020).…”
Section: Study Areamentioning
confidence: 99%
“…Simultaneously, establishing an Anatidae ecological monitoring network is essential. Regularly monitoring Anatidae numbers, distribution, and migration will enable prompt issue detection and the implementation of necessary conservation measures [53].…”
Section: Protection Measures and The Epidemic Disease Source Preventi...mentioning
confidence: 99%